2021
DOI: 10.30685/tujom.v6i1.106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of guilt and the love of money on avoiding luxury clothing brand purchasing

Abstract: Consumers may avoid purchasing luxury brands, which may cause negative feelings, such as low income and moral beliefs. It is essential to know the factors that affect the intentions to avoid luxury consumption and develop suggestions for businesses that market these products and know this relatively less studied aspect of consumer behaviour. In this study, the feeling of guilt arising from purchasing high-priced luxury clothing products and the effect of love of money, which expresses the individual's approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Mallett (2012) also concluded that individuals experience eco‐guilt when they do harmful things to the environment and are more likely to voluntarily adopt green efforts such as recycling (Ölander & Thøgersen, 1995). The feeling of guilt is also often aroused in luxury consumption, which may reduce consumers' purchase of high‐priced products (Bozacı, 2021) or lead them to consume luxury products in a sustainable manner (Ki & Kim, 2016).…”
Section: Studymentioning
confidence: 99%
“…Mallett (2012) also concluded that individuals experience eco‐guilt when they do harmful things to the environment and are more likely to voluntarily adopt green efforts such as recycling (Ölander & Thøgersen, 1995). The feeling of guilt is also often aroused in luxury consumption, which may reduce consumers' purchase of high‐priced products (Bozacı, 2021) or lead them to consume luxury products in a sustainable manner (Ki & Kim, 2016).…”
Section: Studymentioning
confidence: 99%